The hidden power of LOTUS 1-2-3 : using macros - Ridington, Richard W.; Williams, Mark M. (Bowie, MD : Brady Communications Co., 1985)
A practical guide to advanced macro programming in Lotus 1-2-3, covering macro techniques, looping, menu creation, automation, custom commands, and tailored spreadsheet control.
Abstracts Includes index.
Includes bibliographical references and index.
Keywords: Lotus 1-2-3 (Computer file).; Business -- Data processing; Lotus 1-2-3 (Computer program).; Electronic spreadsheets; Spreadsheet software; Computer programs; Computer manuals